Cerebral Venous Thrombosis Complicating Severe Preeclampsia in the Postpartum Period. Issue 2 (June 2015) - Ilkhchoui, Y.; Szabo, E.E.; Gerstein, N.S.; Jaime, F.
<x xml:space="preserve">Abstract</x> (J Clin Anesth. 2014;26(2):143–146)